Selection of MicroRNAs Associated between Neural Stem Cells and Multiple Sclerosis : - Taleahmad, Sara; Mandegarfard , Sepideh; Moradi, Ali; Bereimipour, Ahmad; Hoseinian, Mohammad (Galen Medical Journal, 2022)
Background: Diagnosis and treatment of multiple sclerosis (MS) in its advanced state have been one of the medical community's concerns so far. Cell therapy has been a modern and successful treatment. However, it has not yet been effective enough to treat MS. This study aimed to find the relationship between neural stem cells (NSCs) and MS, and by considering important signaling pathways of pathogenesis, the most important microRNAs (miRNAs) for its diagnosis and treatment were investigated. Materials and Methods: Using the bioinformatics approaches and appropriate databases, the relationship between NSCs and MS were recognized, and after obtaining common genes between them, the protein products by them were evaluated. Finally, after nominating essential genes, we isolated and analyzed the microarrays involved in these pathways. Results: In the first step, 76 upregulated and 1600 down-regulated common genes between NSCs and MS were recognized. Upregulated genes obtained axon guidance, NCAM, and RHO signaling pathways, and the cell cycle, RNA metabolism, and DNA repair signaling pathways by down-regulated genes. Then, high-expression PAK3, ROBO2, and LIMK2, and low-expression AURKA, BIRC5, BLM, and BRCA1 proteins were identified. Accordingly, high-expression miRNAs included hsa-miR-4790-5p, hsa-miR-4281, and hsa-miR-4327, but low-expression miRNAs included hsa-miR-103b, hsa-miR-638, and hsa-miR-4537 were recognized. Conclusion: Our study indicated that the abovementioned important miRNAs have a major role in diagnosing and treating MS.